The role of zero-tillage in climate change mitigation - Cooper, Hannah (2020)
An estimated 11% of the world’s land surface is under cultivation for crop production, and an additional 6.6% of the land will need to come into cultivation to feed a population of 9.1 billion people in 2050. Agricultural soils are a significant source of greenhouse gas emissions, contributing one-fifth of CO2 emissions globally, one-third of CH4 emissions and two-thirds of N2O emissions. Changes in the management of agricultural soils can affect their role as a source or sink in the global carbon cycle, and the scale and composition of their greenhouse gas emissions. Therefore, understanding the role of different crop cultivation regimes in regulating these processes is a key global challenge